Case–Control Study Examining the Association between Allopurinol use and Ischemic Cerebrovascular Disease. (January 2019) - Lai, Shih-Wei; Lin, Cheng-Li; Liao, Kuan-Fu
Few studies focus on the relationship between allopurinol and ischemic cerebrovascular disease. The goal of the study was to investigate the association of long-term therapy of allopurinol with the first-time attack of ischemic cerebrovascular disease in Taiwan. We performed a case–control study using the database of the Taiwan National Health Insurance Program. The case group included 14, 937 subjects aged 20–84 years with the first-time attack of ischemic cerebrovascular disease from 2000 to 2013. The control group included 14, 937 sex-matched and age-matched subjects aged 20–84 years without any type of cerebrovascular disease. Ever use of allopurinol was defined as subjects who had at least a prescription for allopurinol before the index date. The OR and the 95% CI for ischemic cerebrovascular disease associated with allopurinol use were measured by the multivariable logistic regression model. The adjusted OR of ischemic cerebrovascular disease was 0.992 (95% CI 0.989 to 0.996) for subjects with increasing cumulative duration of allopurinol use for every 1 month, compared with never use. In a further analysis, the adjusted OR of ischemic cerebrovascular disease was 0.74 (95% CI 0.57 to 0.96) for cumulative duration of allopurinol use >3 years, compared with never use. Our findings suggest that lone-term therapy of allopurinol >3 years is associated with decreased risk of the first-time attack of ischemic cerebrovascular disease, compared with no allopurinol therapy.